Scutellarin Attenuates Hypertension-Induced Expression of Brain Toll-Like Receptor 4/Nuclear Factor Kappa B - Xingyong Chen; Xiaogeng Shi; Xu Zhang; Huixin Lei; Simei Long; Huanxing Su; Zhong Pei; Ruxun Huang (Hindawi Limited, 2013)
Hypertension is associated with low-grade inflammation, and Toll-like receptor 4 (TLR4) has been shown to be linked to the development and maintenance of hypertension. This study aimed to investigate the effects of scutellarin (administered by oral gavage daily for 2 weeks) on brain TLR4/nuclear factor kappa B-(NF-κB-) mediated inflammation and blood pressure in renovascular hypertensive (using the 2-kidney, 2-clip method) rats. Immunofluorescence and western immunoblot analyses revealed that hypertension contributed to the activation of TLR4 and NF-κB, accompanied by significantly enhanced expression of proinflammatory mediators, such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-18 (IL-18). Furthermore, expression of the antiapoptotic protein, myeloid cell leukemia-1 (Mcl1), was decreased, and the pro-apoptotic proteins, Bax and cleavedcaspase-3 p17 were increased in combined cerebral cortical/striatal soluble lysates. Scutellarin significantly lowered blood pressure and attenuated the number of activated microglia and macrophages in brains of hypertensive rats. Furthermore, scutellarin significantly reduced the expression of TLR4, NF-κB p65, TNF-α, IL-1β, IL-18, Bax and cleaved-caspase-3 p17, and increased the expression of Mcl1. Overall, these results revealed that scutellarin exhibits anti-inflammatory and anti-apoptotic properties and decreases blood pressure in hypertensive rats. Therefore, scutellarin may be a potential therapeutic agent in hypertension-associated diseases.